Pengaruh Pola Asuh Orang Tua Terhadap Kontrol Penggunaan Media Sosial Pada Remaja - Selfiana, Fransiska; Berangka, Dedimus (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2026)
This study aims to analyze the influence of parenting styles on social media usage control among adolescents in Santo Petrus Erom Parish. The phenomenon of excessive social media use among adolescents shows addiction that affects sleep quality, learning concentration, and participation in church activities. This research uses quantitative methods with a simple linear regression analysis approach. The research population consisted of 70 adolescents aged 12-18 years in Santo Petrus Erom Parish, all of whom were used as research samples (total sampling). Data were collected through a Likert scale questionnaire that had been tested for validity and reliability. The results showed that parenting style has a significant influence on social media usage control among adolescents with a significance value of 0.019 (p<0.05), so the alternative hypothesis (Ha) is accepted. The coefficient of determination (R²) of 0.078 indicates that parenting style influences 7.8% of social media usage control, while 92.2% is influenced by other factors not examined. Although its contribution is relatively small, its influence is statistically significant. These findings indicate the importance of parents' active role in guiding children to use social media wisely through setting time limits, content monitoring, open communication, and digital literacy education. This research provides input for parents and the church in designing adolescent mentoring programs in the digital era.